Unavoidable exposure to secondhand smoke in indoor places: a cross-sectional comparison to the Health Japan 21 (second term) objectives, 2022 - Satomi Odani; Takahiro Tabuchi (Komiyama Printing Co. Ltd, 2023)
Background: The second term Health Japan 21 aims at eliminating unwanted exposure to secondhand smoke (SHS) in society; however, the ambiguity of the term "unwanted exposure" complicates the evaluation of the program. In this study, we examined SHS exposure that occurred despite the efforts to avoid it (i.e. unavoidable SHS exposure) as a proxy for "unwanted SHS exposure". Methods: Individuals aged 16-74 responded to a nationwide, Internet-based, self-reported survey. Frequency (daily/≥monthly) of SHS exposure in the past month was assessed for specific places (home/car/restaurant/cafe/bar/workplace/school/pachinko parlor) and any place. Unavoidable SHS was identified when respondents always tried to avoid but were exposed to SHS. The observed prevalence was compared to the target of Health Japan 21 ("Eliminate unwanted SHS exposure", =0%). Analyses were weighted to account for the selectivity of the Internet-based sample. Results: Among overall (N = 25,672), those who always tried to avoid SHS (N = 14,971), and never smokers of combustible tobacco who always tried to avoid SHS (N = 10,416), the prevalence of daily SHS exposure was 12.4%, 5.7%, and 4.2%; ≥monthly SHS exposure was 34.0%, 21.4%, and 17.5%, respectively. Among never smokers, the adjusted prevalence ratio (APR) of daily unavoidable SHS exposure was significantly high in adolescents (age 16-19) (APR = 4.97, vs. age 60-74), less-educated individuals (APR = 2.37, vs. ≥some college education), and heated tobacco product (HTP) users (APR = 8.27, vs. nonusers). Among never smokers, daily unavoidable SHS exposure was highest in the home (3.4%), workplaces (2.3%), and pachinko parlors (1.3%); ≥monthly unavoidable SHS exposure was highest in workplaces (11.4%), restaurants/cafes/bars (10.0%), and the home (7.6%). Conclusions: Daily unavoidable SHS exposure was disproportionately high among adolescents, less-educated individuals, and HTP users. The prevalence of unavoidable SHS exposure did not reach the national target in any of the assessed indoor places; home and workplace were the dominant sources of unavoidable SHS exposure. The lack of comprehensive smoke-free laws provides inadequate protection against SHS that cannot be complemented by individual efforts. The authorities must ensure smoke-free environments for all.